IS IT WORTH TO DISCONTINUE DRUGS BLOCKING THE ACTIVITY OF RENIN-ANGIOTENSIN-ALDOSTERONE SYSTEM IN THE PERI-OPERATIVE PERIOD? - V. V. Lomivorotov; S. M. Efremov; M. N. Аbubаkirov; D. N. Merekin (Вестник анестезиологии и реаниматологии)
Despite significant achievements in the management of patients with cardiac vascular pathology, this type of disorders remains to be the major cause of death all over the world. Patients undergoing surgery and suffering from cardiac vascular diseases face a high risk to develop post-operative complications and lethal outcome and about half of the post-operative lethal cases after non-cardiac surgery are caused by cardiac vascular complications. Inhibitors of angiotensin-converting enzyme as well as angiotensin II receptor blockers are the ones of the most frequently used drugs in cardiology; they have been proved to slow down the progress of the disease, improve life quality and reduce mortality. However, the use of these drugs in pre-operative period can be associated with such adverse events as hypotension and post-operative renal dysfunction. Thus, it is necessary to justify therapy with blockers of renin-angiotensin-aldosterone system in the peri-operative period in the patients undergoing cardiac and non-cardiac surgery.